Response of Summer Ozone to Precursor Emission Controls in the Yangtze River Delta Region - Mao, Yu-Hao; Yu, Shukun; Shang, Yongjie; Liao, Hong; Li, Nan (Frontiers in Environmental Science, 2022)
Surface ozone in the Yangtze River Delta (YRD) in China have significantly increased with the dramatic reduction of anthropogenic nitrogen oxides (NOx) emissions since 2013. As the nonlinearity between ozone and its precursors (i.e., NOx and volatile organic compounds (VOCs)) varies greatly in time and space, we quantify changes of ozone with the co-control of NOx and VOCs anthropogenic emissions in YRD for May–October 2017 by using the GEOS-Chem model. Model evaluations show that GEOS-Chem is in good performance to simulate ozone in YRD. For May–September 2017, most areas in YRD are under a transitional regime but the regions with high anthropogenic emissions including Shanghai and southern Jiangsu are under a VOCs-limited regime. In October, basically the entire YRD is under a VOCs-limited regime. Generally, reducing VOCs emissions only is the most effective method for ozone control in YRD. Nanjing is under a VOCs-limited regime in May, June, September, and October, and under a transition regime from July to August. The VOCs/NOx emission reduction ratio of 1:1 is effective for ozone mitigation in Nanjing (Shanghai) in May, June, and September (for May–September); the corresponding ratio is 2:1 in October. Hangzhou belongs to a transitional regime for May–September and is under a VOCs-limited regime in October. Reducing NOx emissions only would control ozone in Hangzhou for May–September, while the VOCs/NOx emission reduction ratio of 1:1 is favor to reduce ozone in October. GEOS-Chem tagged ozone simulation shows that ozone problem in YRD is caused by the joint effect of local generation and regional transport. Local generation (19.0~50.7%) is generally the largest contributor to monthly mean ozone concentrations in Jiangsu and Shanghai, Zhejiang, and central eastern China; the contribution of ozone from regions outside YRD is larger in spring and autumn (42~76.0%) than in summer (23.3~51.8%). According to the requirements of the Chinese government for NOx and VOCs emission reduction by 2025, the growth of ozone would be stopped in YRD for May–September but likely to continue in October. Our study thus would provide a scientific base to guide the precise emission reduction strategies for ozone control in YRD.